Exploring traditional African beliefs with regard to mental health, health-seeking behaviour, and treatment adherence: A systematic review - Krwece, Akhona (University of Western Cape, 2021)
Magister Artium (Psychology) - MA(Psych) === Previous research indicates that mental health conditions contribute to the global burden of disease. Despite these findings, issues surrounding mental health are still plagued with ignorance and stigma. In recent years’ mental health has taken priority and is increasingly being recognized as an important public health and development issue. Research has found that belief systems play a crucial role in the conceptualisation of mental health and health-seeking behaviour. The exploration of these belief systems gives valuable insight on issues related to health-seeking and treatment adherence behaviours. This study looks specifically at traditional African beliefs and perceptions of mental health. The motivation of this study is to explore how these beliefs and perceptions impact on health-seeking and treatment adherence behaviours. The study poses the following research question: What current literature exists on traditional African beliefs and perceptions about mental health? To achieve this, the study employs a systematic review methodology to assess the methodological rigour of literature on traditional African belief systems. A systematic search in eleven databases was conducted to find relevant literature published between the years 2008 and 2019 with only qualitative research studies.